2009
DOI: 10.1098/rspb.2009.0127
|View full text |Cite
|
Sign up to set email alerts
|

Trill consistency is an age-related assessment signal in banded wrens

Abstract: Older males tend to have a competitive advantage over younger males in sexual selection. Therefore, it is expected that signals used in sexual selection change with age. Although song repertoire size in songbirds is often mentioned as an age-related trait, many species, including the banded wren (Thryothorus pleurostictus), do not increase their repertoires after the first year. Here, we show that banded wrens reproduce the trill notes in their songs with less variability between them (i.e. more consistently) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 46 publications
6
88
1
Order By: Relevance
“…Interestingly, despite its exclusion from many conceptual frameworks of complex signalling, research exploring 'consistency' in signalling (i.e. redundancy) is gaining momentum [59][60][61][62], and this growing research focus may benefit tremendously from the recognition that repetition and consistency might relate to both system redundancy and modularity (discussed below). Redundancy provides a certain degree of robustness to a system [58].…”
Section: System Properties Of Animal Signallingmentioning
confidence: 99%
“…Interestingly, despite its exclusion from many conceptual frameworks of complex signalling, research exploring 'consistency' in signalling (i.e. redundancy) is gaining momentum [59][60][61][62], and this growing research focus may benefit tremendously from the recognition that repetition and consistency might relate to both system redundancy and modularity (discussed below). Redundancy provides a certain degree of robustness to a system [58].…”
Section: System Properties Of Animal Signallingmentioning
confidence: 99%
“…For example, in adult banded wrens, Thryothorus pleurostictus, tropical mockingbirds, Mimus gilvus, and great tits, Parus major, syllable consistency increases by ~3% over 1 year de Kort et al, 2009;RiveraGutierrez et al, 2010). In zebra finches, Taeniopygia guttata, the consistency of syllable structure is ~40% higher for adult males 4years and older than for adult males less than 6 months old (Kao and Brainard, 2006).…”
Section: Functional (Behavioral) Studies Of Vocal Consistencymentioning
confidence: 99%
“…In a number of songbirds, including tropical mockingbirds, banded wrens, great tits and zebra finches, vocal consistency increases with age, and it has been proposed that older males have more consistent songs because of increased opportunity for vocal practice and refinement (Botero et al, 2008;de Kort et al, 2009;Kao and Brainard, 2006;Pytte et al, 2007;Rivera-Gutierrez et al, 2010). Similarly, it has been proposed that vocal practice contributes to the higher levels of vocal consistency during the breeding season than during the non-breeding season.…”
mentioning
confidence: 99%
“…We investigated the effects of the in ovo treatment and the subsequent testosterone implantation on song consistency, which reflects the temporal and spectral stereotypy of a song, because testosterone is thought to trigger the change from plastic, juvenile song, as sung in fall by first year canaries to consistent, stereotyped adult song, which is typically sung in spring after song crystallisation (Marler et al 1988;Catchpole and Slater, 2008;Nottebohm, 2005;Williams, 2004). Song consistency has also been suggested to reflect a male's quality de Kort et al, 2009;Sakata and Vehrencamp, 2011). Furthermore, a recent study in male canaries showed that implanting testosterone rapidly increased song activity (Sartor et al, 2005;Boserèt et al, 2006).…”
Section: Introductionmentioning
confidence: 99%